Gut Microbiota for Esophageal Cancer: Role in Carcinogenesis and Clinical Implications - Zhou, Jianfeng; Sun, Shangwei; Luan, Siyuan; Xiao, Xin; Yang, Yushang; Mao, Chengyi; Chen, Longqi; Zeng, Xiaoxi; Zhang, Yonggang; Yuan, Yong (Frontiers in Oncology, 2021)
Esophageal cancer (EC) is a common malignant tumor of the upper digestive tract worldwide. The microbiota situated at digestive tract epithelium comprises a huge number of microorganisms that adapt to immune defense and interact with the host to constitute symbiotic networks, which affect many physiological processes such as metabolism, tissue development and immune response. It has previously been observed that there are microbial compositional changes in patients with EC, which provides an important opportunity to advance clinical applications using our findings on the gut microbiota. For example, microbiota detection can be used as biomarkers for screening and prognostic, adjusting microorganisms can be developed to treat cancer and decrease adverse effects of treatment. This review aims to give an outline of the gut microbiota in esophagus neoplasia, including involved mechanisms of microbiota-related carcinogenesis and the prospect of utilizing the microbiota as EC biomarkers and treatment targets. These findings have important implications for translating the use of gut microbiota to clinical application.